Islamic Law Thoughts: Itsbat Nikah According to A Compilation of Islamic Law and Fiqh Syafi`iyah - Wildan, T.; Ismail, Syawaluddin (State of Islamic Institute Langsa, 2023)
The provisions of Isbāt nikāh have differences in the views of the Compilation of Islamic Law (KHI) and the Shafi'i school of jurisprudence (Fiqh Syafi’iyah). These differences have attracted the attention of the author to study them. The method used in this research is descriptive comparative analysis, which involves examining and comparing a problem through explanation, interpretation, recording, and data analysis. The research results indicate that isbat nikah is found in the Compilation of Islamic Law and the Shafi'i school of jurisprudence. However, the term Isbāt nikāh is not mentioned in the Shafi'i school of jurisprudence. In contrast, the KHI specifically regulates this issue in Article 7, paragraphs 1, 2, 3, and 4. The provisions of isbat nikah, according to the KHI and the Shafi'i school of jurisprudence, differ significantly. Almost all the provisions of isbat nikah in the KHI are not found in the Shafi'i school of jurisprudence.